The enhancement mechanism of Yb3+/Tm3+/12CaO·7Al2O3 via Li+ incorporation and temperature sensing applications. (December 2019) - Wang, M.; Wang, R.; Li, Y.; Lin, N.; Xu, Y.
Abstract: The manipulation of enhancing the upconversion emission and temperature sensing for obtaining new bifunctional materials is significant. However, the application of upconversion materials suffers from low luminescence efficiency and low temperature sensitivity. Herein, the enhancement of upconversion luminescence and high-temperature sensing in the Yb 3+ /Tm 3+ /12CaO·7Al2 O3 system (the host material can work at temperatures greater than 1000 °C with high melting points and strong mechanical properties) have been achieved with Li + ions doped via the solid-state reaction method. The blue upconversion emission was increased ∼43 times with Li + ion doping, mostly due to the distorted crystal field (replacing Ca 2+ site, occupying interstitial space and oxygen vacancy) and the reduction of quenched ions. And the energy transfer efficiency increase from ∼37.6% to ∼70.5% with the doping of Li + ions. Furthermore, a high S a of 2.33 10 −3 K −1 was obtained. These results provided a new platform for the design of a blue light visible laser and optical temperature sensor. Highlights: It was the first time that Li+ was doped in C12A7 for enhancing the fluorescence intensity. The enhancement mechanism was discussed. High-temperature sensitivity coefficient was obtained.